Вечерние огни: [стихотворения] / Афанасий Фет - Фет Афанасий Афанасьевич (Великие поэты, 2012)
Экземпляры: ФО-2 (20180607) / Инвентарный номер: 51495z1 / Цена: / Авт.знак: Ф 45 / ГРНТИ: 17.82.10 / ББК: 84(2Рос-Рус)1